1979
DOI: 10.1148/131.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Occlusion of the Gastroduodenal Artery

Abstract: The gastroduodenal arteries of 7 patients were occluded for treatment of duodenal bleeding in 4, hepatic devascularization in 2, and redistribution of blood flow for intra-arterial chemotherapy in one patient. In 6 patients, occlusion was performed with Gianturco coils, and with Gelfoam in one. No major complication was encountered. This approach was successful in the control of bleeding from peptic ulcers, arteriovenous malformation and invasion of duodenum by retroperitoneal metastatic lymph nodes from carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Acute cholecystitis attributed to inadvertent embolisation of the cystic artery was reported following DEB TACE [20]. In order to avoid serious adverse effects or damage to the gastroduodenal territory due to misdistribution of embolic or chemotherapeutic agents, embolisation of the gastroduodenal artery can be performed prior to embolisation [32, 33]. Prophylactic embolisation of nontarget arteries is a well-established approach to protection of non target organs in 90 Y SIR-Spheres embolisation [34].…”
Section: Discussionmentioning
confidence: 99%
“…Acute cholecystitis attributed to inadvertent embolisation of the cystic artery was reported following DEB TACE [20]. In order to avoid serious adverse effects or damage to the gastroduodenal territory due to misdistribution of embolic or chemotherapeutic agents, embolisation of the gastroduodenal artery can be performed prior to embolisation [32, 33]. Prophylactic embolisation of nontarget arteries is a well-established approach to protection of non target organs in 90 Y SIR-Spheres embolisation [34].…”
Section: Discussionmentioning
confidence: 99%
“…A gastric mucosal lesion caused by inflow of chemotherapeutic agents into the right gastric artery is one such complication [15][16][17][18][19][20][21][22][23][24]. To prevent this complication, researchers have noted the efficacy of selectively embolizing the right gastric artery at the time of implantation of the port-catheter system [21,[25][26][27].…”
Section: Objectivementioning
confidence: 99%
“…As a result, only two (1.6%) of 128 patients discontinued scheduled HAIC because of gastrointestinal mucosal lesions. Previous reports have also described the efficacy of selective TAE for arteries that supply blood to extrahepatic adjacent organs to avoid reactive gastric or duodenal mucosal lesions resulting from infusion of chemotherapeutic agents into these organs(7,16,20,24,25). Inaba et al(25) reviewed 217 patients who underwent repeat HAIC and found that only five (2.6%) of 192 patients in whom the right gastric artery was sufficiently embolized before long-term HAIC developed gastric mucosal lesions, whereas nine (36.0%) of 25 patients without sufficient embolization developed such lesions.…”
mentioning
confidence: 99%